PROSPECTS FOR NATIONAL DIGITAL CURRENCIES: DIGITAL YUAN, DIGITAL RUBLE AND DIGITAL SUM IN THE GLOBAL FINANCIAL SYSTEM (Web of Technology: Multidimensional Research Journal, 2025)
The introduction of central bank digital currencies (CBDC) in various countries is emerging as a strategic step toward shaping a new model of global financial relations. This paper explores the specific features of the digital yuan (e-CNY), the digital ruble, and the prospective digital sum. It analyzes the impact of these currencies on cross-border transactions, national economic resilience, digital transformation, and the global financial system. By employing a comparative analysis and reviewing regulatory frameworks, the study identifies key advantages and risks associated with integrating CBDCs into the world economy.